2022
DOI: 10.3390/info13040203
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Machine Learning Approaches in Digital Education: A Systematic Revision

Abstract: The use of artificial intelligence and machine learning techniques across all disciplines has exploded in the past few years, with the ever-growing size of data and the changing needs of higher education, such as digital education. Similarly, online educational information systems have a huge amount of data related to students in digital education. This educational data can be used with artificial intelligence and machine learning techniques to improve digital education. This study makes two main contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 74 publications
(177 reference statements)
3
38
0
Order By: Relevance
“…For UAV deployment problems, many studies use artificial intelligence technology [29,30], such as clustering algorithms [31], deep learning [32,36], particle swarm optimization [33], reinforcement learning [19] and so on. Although the performance between the UAVs and users is improved to a certain extent, the promotion of the performance is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For UAV deployment problems, many studies use artificial intelligence technology [29,30], such as clustering algorithms [31], deep learning [32,36], particle swarm optimization [33], reinforcement learning [19] and so on. Although the performance between the UAVs and users is improved to a certain extent, the promotion of the performance is limited.…”
Section: Discussionmentioning
confidence: 99%
“…For UAV deployment problems, many studies used artificial intelligence technology [29,30], such as clustering algorithms [31], deep learning (DL) [32], reinforcement learning (RL) [19] and so on. Zhang et al [33] adopted the coverage probability as an evaluation index to find the 3D position of UAVs using particle swarm optimization, and they achieved the optimization purpose of maximizing the coverage probability.…”
mentioning
confidence: 99%
“…Different research such as in [41] has confirmed the effectiveness of applying machine learning approaches in digital education for performing intelligent tutoring, raising prediction tasks' performance, working with learning styles, and automation in general. As mentioned in [42], although automated tests could be considered a vital advance in e-learning, however, to date, the use of automated methods for item development and test construction has been limited.…”
Section: Related Workmentioning
confidence: 98%
“…Inadequate facilities, a scarcity of resources, and a shortage of trained teachers are only some of the problems affecting rural India's educational system (Roy, 2020). The advent of Alexa as an educational assistant provides an opportunity to overcome these challenges by providing learners in remote areas with a low-cost, engaging medium that can enhance standard teaching methods (Munir et al, 2022). Students can participate in collaborative projects, develop their critical thinking abilities, and gain access to a wide range of information and resources by using Alexa.…”
Section: Literature Reviewmentioning
confidence: 99%